Incorporation of Nanocellulose for Enhanced Electro-Mechanical properties in Novel Ionogel Composite - Suen, Ji Wei (Curtin University, 2023)
Ionogels are materials with ionic liquid confined in a polymer matrix, this combination has allowed vast practical application of ionogel. However, the main problem associated with ionogel is the low ionic conductivity, which is enhanced at the expense of mechanical strength. Thus, methyl cellulose is a potential filler to be incorporated in ionogel due to the copious presence of the amorphous region and hydroxyl group, which facilitates simultaneous augmentation of ionic conductivity and mechanical properties.